2022
DOI: 10.1055/s-0042-1750093
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of 1998 Patients Diagnosed with Brain Death between 2011 and 2019 in Turkey

Abstract: Background Organ transplantation reduces mortality and morbidity in patients with end-stage organ failure. The number of living organ donations is not enough to meet the current organ transplantation need; therefore, there is an urgent need for organ donation from cadavers. We aimed to determine the organ donation rates and reveal the obstacles against donation. Methods This study is designed as a retrospective multicenter study consisting of eight university hospitals, three training and research ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In two separate studies conducted in Türkiye between 2008–2019 and 2014–2018, it was determined that approximately 55% of the cases were male and the mean age was 49 and 53, respectively. [ 8 , 9 ] In addition, in the study of Sipahioglu et al [ 10 ] examining the cases diagnosed with 1998 brain death between 2011 and 2019, 63.8% were male and 36.2% were female, and the median age of the cases was 38 years. In the cohort study conducted on 69,735 cases in the USA between 2012 and 2016, 56.47% of the cases were male and 43.53% were female.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In two separate studies conducted in Türkiye between 2008–2019 and 2014–2018, it was determined that approximately 55% of the cases were male and the mean age was 49 and 53, respectively. [ 8 , 9 ] In addition, in the study of Sipahioglu et al [ 10 ] examining the cases diagnosed with 1998 brain death between 2011 and 2019, 63.8% were male and 36.2% were female, and the median age of the cases was 38 years. In the cohort study conducted on 69,735 cases in the USA between 2012 and 2016, 56.47% of the cases were male and 43.53% were female.…”
Section: Discussionmentioning
confidence: 99%
“…The primary disease causing permanent brain death in Türkiye has been identified as approximately 50–55% intracranial haemorrhage. [ 8 , 10 , 15 ] In Spain with 1844 cases and in Italy with 1286 cases, the primary disease causing death was found to be intracranial hemorrhage in 56% and 52%, respectively. [ 16 , 17 ] In the study literature, the primary disease of cases with brain death was found to be hemorrhagic cerebral damage in 47% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations